2016
DOI: 10.1016/j.bone.2015.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with BMP-2 and a systemic RANKL inhibitor enhances bone healing in a mouse critical-sized femoral defect

Abstract: Recombinant human BMP-2 (rhBMP-2) is a potent osteoinductive agent, but has been associated not only with bone formation, but also osteoclastogenesis and bone resorption. Osteoprotegerin (OPG) is a RANKL inhibitor that blocks differentiation and function of osteoclasts. We hypothesized that the combination of local BMP-2 (recombinant protein or a product of gene therapy) plus systemic OPG-Fc is more effective than BMP-2 alone in promoting bone repair. To test this hypothesis we used a mouse critical-sized femo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 47 publications
1
31
0
1
Order By: Relevance
“…With the advent of different potential therapeutic agents (Gibson et al, 2015; Li and Whitehead, 2010) along with a handful of genes implicated in CCM signaling (Zhou et al, 2015) and phenotypic variations (Choquet et al, 2014), a sensitive, reliable and rapid way of determining their impact on CCM genesis and progression is desirable. The use of the micro-CT technique to assess therapeutic interventions is already being applied in other disease states (Bougioukli et al, 2015; Rusckowski et al, 2016). Similarly, micro-CT imaging is already being relied on in pre-clinical transgenic models involving genetic alterations and transcriptional modifications (Huesa et al, 2015; Keller et al, 2013).…”
Section: Applications and Discussionmentioning
confidence: 99%
“…With the advent of different potential therapeutic agents (Gibson et al, 2015; Li and Whitehead, 2010) along with a handful of genes implicated in CCM signaling (Zhou et al, 2015) and phenotypic variations (Choquet et al, 2014), a sensitive, reliable and rapid way of determining their impact on CCM genesis and progression is desirable. The use of the micro-CT technique to assess therapeutic interventions is already being applied in other disease states (Bougioukli et al, 2015; Rusckowski et al, 2016). Similarly, micro-CT imaging is already being relied on in pre-clinical transgenic models involving genetic alterations and transcriptional modifications (Huesa et al, 2015; Keller et al, 2013).…”
Section: Applications and Discussionmentioning
confidence: 99%
“…[3, 62] OPG has been shown to have inhibitory potential in breast cancer-induced bone destruction. [63]…”
Section: 4 Therapeutic Management Of Cibpmentioning
confidence: 99%
“…BMP2 was also suggested to protect the growth and decrease the apoptosis of NP cells (22), but the exact mechanism remains unclear. An animal model demonstrated that combination therapy of BMP2 and a receptor activator of nuclear factor κB ligand inhibitor promoted bone healing in a critical-sized femoral defect mouse model (23). Additionally, BMP2 inhibited the growth and metastasis of hepatocellular carcinoma by inhibiting the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) pathway, which serves an important role in osteogenesis (24,25).…”
Section: Introductionmentioning
confidence: 99%